Consumer Buying Behavior in the Age of Digital Marketing: An Exploratory Study of the Opinions of a Sample of Shoppers Through Digital Marketing Channels - Abdullah, Anees; Abdullah, Mohammad; Jalal, Ahmed (The Arab Journal of Administration, 2022)
Purpose: The aim behind selecting this topic for study is to find out the Impact of digital marketing channels (mobile marketing, marketing through social media) on the various stages of purchasing decision-making for products by the digital consumer. Research methodology and tools: The current research used the descriptive analytical method to describe the research variables and the nature of the relationship between them. Results: One of the most important findings of the research is that there is a significant effect of the selected digital marketing channels in helping shoppers to act in all stages of digital purchasing decision-making for products, especially in the stage of making a purchase decision. Originality/Value: This research is one of the leading researches in the field of digital marketing and digital consumer behavior locally and in the Arab world. The researchers have developed a new scale to analyze the role of digital marketing channels during the various stages of digital purchasing decision-making without the need to ask questions for the stages of purchasing decision-making and others about digital marketing channels Separately according to the concept of the independent variable and the dependent variable.